A Comparative Study on the Usage of RON68 and Naphtha in an HCCI Engine - Emre Yılmaz (International Journal of Automotive Science and Technology, 2020)
The depletion of fossil fuels as a result of excessive use and increased environmental pollution brought up the research of environmentally conscious and renewable alternative fuels. The alternative fuel to be considered for internal combustion engines should not decrease the performance of the engine too much and positively affect the exhaust emissions. It is also important that this fuel should provide some specifications such as easy producibility, low cost, availability and usability in internal combustion engine without modification. Low temperature combustion modes are promising technologies providing nearly zero NOx and soot emissions and currently a lot of researcher has focused on this technology. In this experimental study naphtha was tested in an HCCI engine. In order to examine and understand the effects of the naphtha on HCCI mode a comparison study was also conducted by using RON68. Maximum imep was computed as 3.23 and 3.32 bar with RON68 and naphtha respectively at λ=1.7. SOC was determined 5.4 °CA and 5.76 °CA ATDC with naphtha and RON68 at λ=2. CA50 is far away from TDC fact that net work decreases. Maximum ITE was calculated as 45.42% and 46.07% at λ=2 with RON68 and naphtha respectively.